2019
DOI: 10.1128/jvi.01480-18
|View full text |Cite
|
Sign up to set email alerts
|

Broad Recognition of Circulating HIV-1 by HIV-1-Specific Cytotoxic T-Lymphocytes with Strong Ability to Suppress HIV-1 Replication

Abstract: HIV-1-specific cytotoxic T-lymphocytes (CTLs) with strong abilities to suppress HIV-1 replication and recognize most circulating HIV-1 strains are candidates for effector T cells for cure treatment and prophylactic AIDS vaccine. Previous studies demonstrated that the existence of CTLs specific for 11 epitopes was significantly associated with good clinical outcomes in Japan, although CTLs specific for one of these epitopes select for escape mutations. However, it remains unknown whether the CTLs specific for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 60 publications
2
28
0
Order By: Relevance
“…However, a non-synonymous substitution, E203D, was observed in CTL epitope DTINEEAAEWDR. The selection of this epitope for immune escape strains has been previously described ( Murakoshi et al, 2019 ). However, the substitution has also been shown not to impact the epitope’s immunogenicity as a vaccine construct ( Ondondo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a non-synonymous substitution, E203D, was observed in CTL epitope DTINEEAAEWDR. The selection of this epitope for immune escape strains has been previously described ( Murakoshi et al, 2019 ). However, the substitution has also been shown not to impact the epitope’s immunogenicity as a vaccine construct ( Ondondo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the West African epicenter having one of the highest numbers of diverse circulating HIV-1 strains, very few longitudinal studies on HIV-1 have been reported from the region. Escape due to CTL epitopes, which is driven by frequencies of non-synonymous and synonymous substitutions ( Kosakovsky Pond et al, 2008 ; Garcia-knight et al, 2016 ), outside the functionally conserved region may be a crucial factor to consider in the design of therapeutic and universal HIV vaccines ( Murakoshi et al, 2019 ). They may also provide opportunities for compensatory mutations on replicative fitness ( Crawford et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…These mutations critically affect suppression of HIV-1 replication by T cells specific for these protective epitopes (4,(26)(27)(28), suggesting a critical effect of these mutations on HIV-1 control by T cells specific for these protective epitopes. On the other hand, recent studies showed that HLA-APs are not present in 10 of 11 protective T cell epitopes among HIV-1 subtype B-infected Japanese individuals (13,29). Thus, the accumulation of escape mutations in the protective epitopes is a rare event in subtype B-infected Japanese individuals.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies on HIV-1 subtype B-infected Japanese individuals demonstrated that HLA-B*52:01-restricted HIV-1-specific CD8 + T cells for 4 epitopes (GagMI8 [Gag 198 to 205], GagWV8 [Gag 316 to 323], GagRI8 [Gag 275 to 282], and PolSI8 [Pol 654 to 661]) have the ability to suppress HIV-1 replication both in vivo and in vitro ( 6 , 44 ). Of these epitopes, GagMI8, GagWV8, and PolSI8 are conserved ones among the subtype B viruses, whereas GagRI8 has 3 substitutions at Gag280 (Gag280S, Gag280A, and Gag280V) in 26% of HIV-1 subtype B-infected Japanese individuals ( 6 , 45 ). A previous study on HLA-associated HIV-1 polymorphisms in HIV-1 subtype B-infected Japanese individuals showed that Gag280S and Gag280A accumulate in HLA-B*52:01 + individuals, whereas Gag280V do not ( 46 ), suggesting that Gag280S and Gag280A are escape mutations selected by HLA-B*52:01-restricted RI8-specific T cells.…”
Section: Introductionmentioning
confidence: 99%